Trial-centrism in the Declaration of Helsinki: A Challenge for Post-Study Access and Preventing Data Colonialism in AI-Driven Health Research - Haidar, Hazar; Shamsi Gooshki, Ehsan (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This letter proposes extending the post-trial provisions of the updated Declaration of Helsinki beyond pharmaceutical drugs to include AI tools, particularly those developed using data from low- and middle-income countries. Such an extension would help prevent data colonialism and ensure more equitable access to these tools, fostering fairness in global health research.